ESTIMATION OF TRIANGULAR LABYRINTH SIDE WEIR DISCHARGE CAPACITY USING SCHMIDT APPROACH - Ikinciogullari, Erdinc; Emiroglu, Muhammet Emin (Yildiz Technical Univ, 2019)
The labyrinth side weir is a new type of weir and a flow diversion apparatus. Labyrinth side weirs could overflow more discharge when compared to classical side weirs. The present study focused on the estimation of triangular labyrinth side weir discharge coefficients using the Schmidt approach. An accurate discharge coefficient should be estimated for the hydraulic design. In the study, various weir included angles, weir opening lengths, crest heights, flow depths, and Froude numbers were considered to estimate the flow characteristics of the labyrinth side weir. 2623 experimental runs were conducted for the triangular side weir. Furthermore, to estimate the discharge capacity, the nape height was determined at two (as proposed by Schmidt) and three points in the present study. The compatibility of the average nape height that was proposed by Schmidt was examined with supplementary laboratory tests. Furthermore, the findings were compared to the literature and confirmed the usability of the Schmidt approach. This study demonstrated that the Schmidt approach was consistent with the tendencies in the literature in determining the discharge capacity and produced a useful graphical presentation for hydraulic designers. The Schmidt approach was quite reliable in calculating triangular labyrinth side weir discharge capacity.
Keywords: Side weirs; discharge coefficient; schmidt approach; discharge capacity; de marchi approach; triangular labyrinth side weirs